Extension services in coastal aquacultrure : need for a public and private partnership - Kumaran, M; Krishnan, M; Ravichandran, P (Indian Journal of Fisheries, 2011)
Aquaculture extension is an interface between aquaculture research and its end users linking the duo. Two parallel streams of public and private funded fishery extension services operate in the system. The present study conducted among both the extension agents to perform a juxtapose comparison of the above two with respect to personal and operational variants. The study revealed that both the group differ significantly in terms of extension approach and methods, information behaviour, linkage with fishery R&D, frequency of contact, age, education, effectiveness and accessibility. The study suggested that both the extension streams ought to work as partners of extension than running a parallel regime. SWOT analysis of the fishery extension service was also reported